Pengembangan Modul Pelatihan Pedagogical Content Knowledge (PCK) Dalam Meningkatkan Kompetensi Profesional dan Kompetensi Pedagogik Guru Matematika SMP - Wulandari, Mega Retno; Iriani, Ade (Universitas Kristen Satya Wacana, 2018)
The research objectives are to describe the training that has been held so far and its weaknesses and to develop PCK training modules in order to improve the pedagogical and professional competence of mathematics teachers. This type of research is research and development. The research subjects were the MGMP Coordinator and junior high school mathematics teacher. Data collection techniques are observation, interviews, documentation studies, and tests. Data analysis techniques use mixed methods. The PCK training module was developed using the Sugiyono model, taking 7 stages namely potential and problems, data collection, product design, design validation, design revisions, limited trials and product revisions. Module validation tests are carried out by module experts, PCK experts, and prospective users. Research results: 1) Training for junior high school mathematics teachers have been focused on the dissemination of the 2013 curriculum and PCK training has never been held; 2) The weakness of the training that has been held so far: material from the powerpoint print out presented by the speaker, when the training collided with teaching activities in the school, the training material was only about the 2013 curriculum; and 3) PCK training modules that have been developed are feasible to use.